Desenvolvimento e validação do índice de vulnerabilidade de famílias a incapacidades e dependência (IVF-ID) - Amendola, Fernanda; Alvarenga, Márcia Regina Martins; Latorre, Maria do Rosário Dias de Oliveira; Oliveira, Maria Amélia de Campos (Revista da Escola de Enfermagem da USP, 2014)
This exploratory, descriptive, cross-sectional, and quantitative study aimed to develop and validate an index of family vulnerability to disability and dependence (FVI-DD). This study was adapted from the Family Development Index, with the addition of social and health indicators of disability and dependence. The instrument was applied to 248 families in the city of Sao Paulo, followed by exploratory factor analysis. Factor validation was performed using the concurrent and discriminant validity of the Lawton scale and Katz Index. The descriptive level adopted for the study was p < 0.05. The final vulnerability index comprised 50 questions classified into seven factors contemplating social and health dimensions, and this index exhibited good internal consistency (Cronbach’s alpha = 0.82). FVI-DD was validated using both the Lawton scale and Katz Index. We conclude that FVI-DD can accurately and reliably assess family vulnerability to disability and dependence.